El caso de Papá Noel - Friedrich, Joachim, 1953- (Friedrich, Joachim, 1953- 4 1/2 Freunde., 2003)
Charly and his friends in the detective club set out to prove a gang of delinquents are committing crimes disguised as Papá Noel.